Pengembangan Usaha Terhadap Perempuan Bali Pasca Perceraian Dari Perkawinan Campuran Bermuatan Gender Dalam Hukum - Ni Ketut Sari Adnyani (Jurnal Ilmiah Raad Kertha, 2019)
This study aims to examine the opportunities for Balinese women in the field ofbusiness development after divorce from mixed marriages, prioritizing the principle ofgender responsiveness into awig-awig, the application of the burden of tolerance to102menyama braya, the status of krama istri, and carrying out the obligation to dance at thetemple. Tri Kahyangan is the goal of the gender content in the law of the business beingdeveloped. The research method in this study is sociological jurisprudence, and the typeof research is analytic study of legal materials that adopt women's rights in the businessworld. The binding legal material refers to the Republic of Indonesia State ConstitutionArticle 18 B paragraph (2) and the Traditional Village Awigers which refer to the DecreeNumber 01 / KEP / PSM-3/ MDP / Bali / X / 2010 by the Main Assembly of the PakramanVillage ( MUDP) Bali concerning the division of inheritance of Balinese women withstatus (pradana) has the right to inherit even though they have married and followed herhusband, inheritance in the form of assets can be the main capital for businessdevelopment in the context of business law. The determination of the research subject wascarried out by stratified random sampling. Legal material analysis techniques aredescriptive. The results of the study: Balinese women were given the opportunity to beaccepted as wife's manners based on the pre-marital agreement of the bride, bride'sfamily, and traditional village which contained the provision that in the future if anincident of custom divorce is ready to accept and provide opportunities to carry outroutines such as the wives of their wives in general. The implication of the gender contentin the law is that the consensus reference from the results of the women's traditionalvillage meeting that is the status of widows from mixed marriages is given the opportunityto open business opportunities in the local village area, and is entitled to inheritancegrants in accordance with the provisions adopted by MUDP Bali after obtaining anagreement with the family big through family consultation with the traditional village(dharma pula).